PHOTOBOOK DESIGN FOR TRADITIONAL THAILAND FOOD - Heru Wijayanto Aripradono; Wandi Wandi (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2022)
Photobook is a book or album that contains photos and can be arranged first and then printed in the form of a book. In the Design of Thai Traditional Food photobook which contains a variety of traditional Thai foods that have unique characteristics. The purpose of this study is to introduce traditional Thai food so that people know more about traditional Thai food. The author uses this research method through the stages of the research flow, namely planning, data collection, design and results. In this design the application used is Adobe Photoshop CC 2018. At the data collection stage using interview and observation activities. The results of the design of a traditional food photobook containing Thai food and several locations that have taken photos. The results of the photobook that has been designed with simple design simplicity by using a simple and attractive layout that will be displayed in a slow lifestyle style. The color grading that the author uses is the Adobe Lightroom 5.3 Software application to explain and check colors. the result is the print stage which is printed with a size of 20 x 20 cm. With this photobook, it is hoped that it will provide more information about traditional Thai food for the community.